Estudio geométrico y estructural de la vía Cabo de Lampa - La Pacífico - intersección entre la Guayacanes y Perugachi, perteneciente al cantón Arenillas, provincia de El Oro. - Gómez Merino, Henry Javier (2015)
The route under consideration, which is in poor condition has caused great economic losses for the inhabitants of these areas, making difficult the normal movement of their products, and transit for tourists visiting the canton Arenillas. For this reason this project aims, the study of the way that best meets the geometric and structural characteristics of agreements to the rules of M.T.O.P. To ensure the inhabitants of these sites, and tourists a functional, safe, economical and aesthetic way. Research and inquiry that was conducted using the method of literature research, consultations on websites (web), and research field under exploration and practice at direct contact with study sites. The results of traffic counts, topography, soil studies and analysis of the asphalt mix, were considered for the geometric design, structural package, environmental impact study and analysis of budgets. For this we adhere to the rules of M.T.O.P. The route is IV Order, was designed with a design speed of 80 km / h, it has a Long. Of 3930.056 meters, it has a track width of 7.20 meters. It has ditches 0.87 wide and 0.35 Prof. pipeline also has 2 box culverts. The structure; It has a thickness of 5 cm asphalt base class 2, 15 cm, Class 2 sub-base of 20 cm and 0.30 cm improvement. This project is viable it has been tested, approved, and at once the procedures for the execution of the work can be performed by the institution to the appropriate parties.